272 Forage use in stocker programs as part of a sustainable beef production system. (7th December 2018) - Rivera, J; Reuter, R; LaManna, A; Beck, P; Gunter, S
Abstract: The stocker segment of the beef industry in the Southern United States can be described as a system in which a producer purchases lightweight, newly-weaned calves for subsequent grazing. The BW gain from grazing is typically less costly than BW gain in feedlots and profitability is based on the margins between purchase expense and sales value. Following the growing period, the cattle are generally sold to a traditional feedlots for finishing. It is difficult to inventory the number of stocker cattle at specific locations, but some estimates exist. Nevertheless, the stocker segment provides several benefits to the beef industry, the enterprise services of the stocker segment include reduced cost of production, better utilization of forage resources, smoothing the supply flow of finished cattle over the calendar year, and provision of groups of immunocompetent preconditioned cattle to feedlots. Despite these benefits, several issues such as animal health and welfare, lack of infrastructure and a trained workforce, and environmental issues such as carbon and water footprints continue to challenge stocker producers. Because of these challenges, research opportunities abound in the stocker segment with improved crop-forage systems and tillage management having the potential to increase the sustainability of the stocker segment. In addition, new technology, such as novel, long-acting pharmaceuticals, devices that can remotely deliver pharmaceuticals, automation of sensors and algorithms to enable precision supplementation and measure production and environmental sustainability variables, all have the potential to help address these challenges. Many of these newer technological approaches have the potential to improve and ease the adoption of known best management practices.